2013
DOI: 10.1161/circulationaha.112.000790
|View full text |Cite
|
Sign up to set email alerts
|

Tumors Metastatic to the Heart

Abstract: Downloaded from Goldberg et al Tumors Metastatic to the Heart 1791cardiac metastases in 2 recent large case series. 1,6 Tumor metastasis to the pericardium may initially result in pericarditis, with subsequent development of serosanguineous or hemorrhagic malignant pericardial effusions. 5,9,10 Depending on their size and rate of accumulation, malignant pericardial effusions may be symptomatic or silent. 5,9,10 Slow accumulation of pericardial effusions is unlikely to cause hemodynamic compromise, even with up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
266
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(286 citation statements)
references
References 18 publications
3
266
0
17
Order By: Relevance
“…Cardiac dysfunction, such as acute coronary syndrome, can also be observed if the myocardium is replaced by tumor cells (1). In this case, the autopsy examination did not show myocyte degeneration, interstitial fibrosis or direct replacement of the myocar- dium with tumor cells but revealed disruption of the cardiac conduction system due to myocardial metastasis.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Cardiac dysfunction, such as acute coronary syndrome, can also be observed if the myocardium is replaced by tumor cells (1). In this case, the autopsy examination did not show myocyte degeneration, interstitial fibrosis or direct replacement of the myocar- dium with tumor cells but revealed disruption of the cardiac conduction system due to myocardial metastasis.…”
Section: Discussionmentioning
confidence: 78%
“…Cardiac metastasis is found at autopsy in up to 10% of patients with known malignancies (1). Lung cancer is reported to be the most common malignancy that causes cardiac metastasis followed by breast cancer and hematologic malignancies (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case signified the necessity of the rapid diagnose and timely treatment at such status. Nevertheless, the identification of the cardiac mass using the TTE or TEE for some groups of patients is complicated and the risk of misdiagnosis is higher due to the adjacent pathology that has already been diagnosed [8,10,11]. Several studies have shown that patients with recently diagnosed oncological process are at higher risk of the metastatic heart disease [11] and 15 % of the patients with any type of cancer may present with cardiac metastases [10].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of a cardiac mass normally requires a complex differential diagnosis between benign tumors (myxoma, lipoma, papillary fibroelastoma, rhabdomyoma, fibroma, teratoma, Purkinje cells tumors/amarthomas, hemangioma), malignant tumors (angiosarcoma, rhabdomyosarcoma, fibrosarcoma, lymphosarcoma, osteosarcoma, liposarcoma), metastases, tumors that may be either benign or malignant (paraganglioma, mesothelioma) and non-neoplastic masses (intracardiac thrombus, endocarditis vegetation, lipomatous hypertrophy of interatrial septum, pericardial cyst, large coronary artery aneurism, crista terminalis) [6,7]. However, due to the clinical history and condition of the patient the possibility excluded was that the mass at the left side of the interventricular septum was a benign tumor.…”
mentioning
confidence: 99%